Commentary on “T.G. Ritto, M.R. Escalante, Rubens Sampaio, M.B. Rosales, Drill-string horizontal dynamics with uncertainty on the frictional force, Journal of Sound and Vibration 332 (2013) 145-153” - Ritto, Thiago (2016)
The goal of this article is to clarify some points of the formulation presented in the “T.G. Ritto, M.R. Escalante, Rubens Sampaio, M.B. Rosales, Drill-string horizontal dynamics with uncertainty on the frictional force, Journal of Sound and Vibration 332 (2013) 145-153”.